2010
DOI: 10.1007/s00018-010-0532-2
|View full text |Cite
|
Sign up to set email alerts
|

Intron creation and DNA repair

Abstract: The genesis of the exon-intron patterns of eukaryotic genes persists as one of the most enigmatic questions in molecular genetics. In particular, the origin and mechanisms responsible for creation of spliceosomal introns have remained controversial. Now the issue appears to have taken a turn. The formation of novel introns in eukaryotes, including some vertebrate lineages, is not as rare as commonly assumed. Moreover, introns appear to have been gained in parallel at closely spaced sites and even repeatedly at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Under certain conditions, genes experience higher frequencies of both double-strand breaks (DSBs) and point mutations (Shee et al 2011; Kim and Jinks-Robertson 2012). If DSB repair was the predominant mechanism of both intron loss and intron gain, as recently suggested (Li et al 2009; Farlow et al 2011; Ragg 2011; Fawcett et al 2012), intron loss and gain would tend to occur simultaneously in hypermutated genes. This hypothesis and the mutational-hazard hypothesis both predict that introns with higher mutation rates would be preferentially lost.…”
Section: Discussionmentioning
confidence: 82%
“…Under certain conditions, genes experience higher frequencies of both double-strand breaks (DSBs) and point mutations (Shee et al 2011; Kim and Jinks-Robertson 2012). If DSB repair was the predominant mechanism of both intron loss and intron gain, as recently suggested (Li et al 2009; Farlow et al 2011; Ragg 2011; Fawcett et al 2012), intron loss and gain would tend to occur simultaneously in hypermutated genes. This hypothesis and the mutational-hazard hypothesis both predict that introns with higher mutation rates would be preferentially lost.…”
Section: Discussionmentioning
confidence: 82%
“…DNA double-stranded breaks (DSBs) and recombination, which involve repair and recombination processes are essential components of genome compactness. Furthermore, intron insertions are now considered to be resultant of error-based repair of DBSs that is predominantly mediated by non-homologous end joining (NHEJ) as recently reviewed [74], [75]. We report that missing repeats in introns from pufferfishes are most likely due to a higher degree of genome compactness in the tetraodontidae lineage when compared to the medaka/stickleback lineage ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 89%
“…DSBR has recently been proposed to result in intron gain if NHEJ inserts filler DNA that may function as a spliceable intron [4,58]. It has been shown that this filler DNA may be preferentially of mitochondrial origin [59,60].…”
Section: Resultsmentioning
confidence: 99%